1986
DOI: 10.1093/infdis/153.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Prototype Inactivated Hepatitis A Virus Vaccine from Infected Cell Cultures

Abstract: Studies were conducted on the preparation, inactivation, safety, and immunogenicity of a prototype hepatitis A virus vaccine prepared from infected cell cultures. BS-C-1 cells maintained in medium 199 without serum were infected with the HM175 strain of hepatitis A virus and harvested after 21-28 days. The harvested virus preparation contained 6.8-7.4 (log 10) cell culture infectious doses/ml. After exposure to 1:4,000 formalin at 35 C, the infectivity titer decreased 10(6)-fold in 30 hr at an exponential rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Several prototype vaccines have been developed, and are undergoing immunogenicity trials, with efficacy trials planned in the near future. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Until such a vaccine is available, conventional measures such as the promotion of handwashing, use of IG for household contacts of acute cases, and the improvement ofgeneral sanitation will remain important priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Several prototype vaccines have been developed, and are undergoing immunogenicity trials, with efficacy trials planned in the near future. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Until such a vaccine is available, conventional measures such as the promotion of handwashing, use of IG for household contacts of acute cases, and the improvement ofgeneral sanitation will remain important priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Non-human primates are considered the principal models for HAV which more closely mimics many of the aspects of the human disease (Purcell & Emerson 2001, Deinhardt et al 1962, Dotzauer et al 1994). Due to high economical and moral concerns, the feasibility of guinea pigs (Cavia porcellus) in the experimental infection by HAV is considered among the replacement options (Binn et al 1986, Elbert et al 1992, Hornei et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that guinea pigs (Cavia porcellus) could be used in several tests of immunogenicity, effectiveness and safety of vaccines (Binn et al 1986, Flehmig et al 1987, Elbert et al 1992, Mitchell & Galun 2003, Mitchell et al 2006) and in events related to the proper vaccine of hepatitis A (Hornei et al 2001, Burnett et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Dubois, and K.H. Eckels [98,99]. Analysis of strains from international sources showed antigenic similarity and indicated that a vaccine need contain only a single serotype to provide global protection against HAV.…”
Section: Hepatitis a Vaccinementioning
confidence: 99%